MTKD: An Algorithm for Multi-Tier Key Distribution for Securing Group Communication in WSN - Annapurna H S; M. Siddappa (Institute of Advanced Engineering and Science, 2017)
Security is one of the inherent challenges in the area of wireless sensor network. At present, majoroty of the security algorithm are incorporated with massive iterations of cryptography as well as complex mathematical modelling that result in degradation of quality of service. The present paper takes the case study of group communication in wireless sensor network and introduces a significant protocol that assist in generation of joint key with an aid of unique and lightweight cryptography. The outcome of the study was compared with the most significant and standard work of group communication to find that proposed system is in adherence of time and space complexity.